Neuro-Oncology and Radiogenomics: Time to Integrate? - Lasocki, A.; Rosenthal, M.A.; Roberts-Thomson, S.J.; Neal, A.; Drummond, K.J. (American Journal of Neuroradiology, 2020)
SUMMARY: Radiogenomics aims to predict genetic markers based on imaging features. The critical importance of molecular markers in the diagnosis and management of intracranial gliomas has led to a rapid growth in radiogenomics research, with progressively increasing complexity. Despite the advances in the techniques being examined, there has been little translation into the clinical domain. This has resulted in a growing disconnect between cutting-edge research and assimilation into clinical practice, though the fundamental goal is for these techniques to improve patient care. The goal of this review, therefore, is to discuss possible clinical scenarios in which the addition of radiogenomics may aid patient management. This includes facilitating patient counseling, determining optimal patient management when complete molecular characterization is not possible, reclassifying tumors, and overcoming some of the limitations of histologic assessment. The review also discusses considerations for selecting relevant radiogenomic features based on the clinical setting.IDHisocitrate dehydrogenaseIDHmutIDH mutantIDHwtIDH wild-typeWHOWorld Health OrganizationHG2-hydroxyglutaratenCETnon-contrast-enhancing tumorcIMPACT-NOWConsortium to Inform Molecular and Practical Approaches to CNS Tumor Taxonomy